Kreativitas Guru dalam Pembelajaran Sejarah pada Masa Pandemi Covid-19 di SMA Negeri 1 Concong Kabupaten Indragiri Hilir - Dasyuniar Dasyuniar; Bedriati Ibrahim; Asril Asril (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2022)
Learning during the Covid-19 pandemic caused many learning problems, namely the number of students who did not have the means or smartphones to study online, so teachers had to find ways so that problems during online learning could be overcome. This study aims to determine (1). Students' problems in learning (2). Teacher creativity in learning history during the covid-19 pandemic. This study uses a qualitative method. Data collection techniques include: Observation interviews and documentation. The subjects of this study were teachers of history subjects and students of class X.1 IIS, XI IIS at SMA Negeri 1 Concong, totaling 12 people. The data analysis technique uses data reduction, data presentation, data verification and conclusion drawing. The results showed that the learning problems experienced by students at SMA Negeri 1 Concong during online learning were not having a smartphone and an unstable internet network. The creativity of teachers in history subjects at SMA Negeri 1 Concong online learning in class X.1 IIS and XII IIS is by utilizing applications such as facebook messenger, and google form. The creativity of teachers in finding suitable applications to overcome learning problems to continue to carry out online learning is supported by the Facebook Messenger application. Students who do not have smartphones can study with close friends from home and this application can still be used even though they do not have an internet quota and an unstable internet network.